2008
DOI: 10.1073/pnas.0808213105
|View full text |Cite
|
Sign up to set email alerts
|

Selectin catch–slip kinetics encode shear threshold adhesive behavior of rolling leukocytes

Abstract: The selectin family of leukocyte adhesion receptors is principally recognized for mediating transient rolling interactions during the inflammatory response. Recent studies using ultrasensitive force probes to characterize the force-lifetime relationship between Pand L-selectin and their endogenous ligands have underscored the ability of increasing levels of force to initially extend the lifetime of these complexes before disrupting bond integrity. This so-called ''catch-slip'' transition has provided an appeal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
73
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(78 citation statements)
references
References 42 publications
3
73
0
Order By: Relevance
“…We conclusively showed that the shear threshold emerges from the shifting minima in bond failure, owing to the emergence of minima with lower dissociation rates at higher shear rates, and not increasing bond formation rates at higher shear [23]. Further calculations by Beste and Hammer [6], showed when the shear threshold should emerge, and for precisely what conditions, and which molecules. For instance, a key prediction is that the conditions for which the shear threshold will emerge for P-and L-selectin are different, and these results are consistent with experiment [6].…”
Section: Relating Bond Mechanics To Dynamics Of Adhesionmentioning
confidence: 60%
See 2 more Smart Citations
“…We conclusively showed that the shear threshold emerges from the shifting minima in bond failure, owing to the emergence of minima with lower dissociation rates at higher shear rates, and not increasing bond formation rates at higher shear [23]. Further calculations by Beste and Hammer [6], showed when the shear threshold should emerge, and for precisely what conditions, and which molecules. For instance, a key prediction is that the conditions for which the shear threshold will emerge for P-and L-selectin are different, and these results are consistent with experiment [6].…”
Section: Relating Bond Mechanics To Dynamics Of Adhesionmentioning
confidence: 60%
“…Further calculations by Beste and Hammer [6], showed when the shear threshold should emerge, and for precisely what conditions, and which molecules. For instance, a key prediction is that the conditions for which the shear threshold will emerge for P-and L-selectin are different, and these results are consistent with experiment [6]. …”
Section: Relating Bond Mechanics To Dynamics Of Adhesionmentioning
confidence: 99%
See 1 more Smart Citation
“…Efforts to model leukocyte rolling 5,11,12 have assumed randomly distributed P-selectin, which clearly does not capture the biologic situation on endothelial cells. Pselectin is clustered, and this clustering requires CD63.…”
Section: 3 O C T O B E R 2 0 1 1 I V O L U M E 1 1 8 N U M B E R mentioning
confidence: 99%
“…An alternative definition of the catch-slip efficiency associated with the presence of both a maximum and a minimum in the force-dependent bond lifetime is given in Beste and Hammer. 5 The deformation model presented above has been successfully used to describe the anomalous dependence of the bond lifetime on the applied force in the P,L-selectins/PSGL-1 18 and actin/myosin 22 catch bonds.…”
Section: Deformation Model Of Enzyme Catalysis In the Presence Of Forcementioning
confidence: 99%